Amoebic colitis: A case series of a recurring missed diagnosis. Issue 3 (22nd December 2020) - Abasszade, Joshua Haron; Little, Robert; Yeaman, Fiona; Robertson, Marcus; Bell, Sally
Abstract: Entamoeba histolytica, a pathogenic protozoan that causes amoebiasis, remains the second leading cause of death from parasitic infections worldwide. We present a case series of patients presenting to metropolitan tertiary gastroenterology units in Melbourne, Australia, highlighting the complexities of diagnosing amoebic colitis and the potential for misdiagnosis. These cases illustrate four key lessons in the identification of amoebic colitis: (i) obtaining a thorough travel and exposure history, (ii) having a high index of suspicion, (iii) understanding the limitations of available investigations, and (iv) being aware that amoebic colitis may masquerade as other common conditions. Abstract : Entamoeba histolytica is the pathogenic protozoan responsible for amoebic colitis, a common parasitic infection, and the second leading cause of death from parasitic infections worldwide. The clinical presentation of amoebic colitis is varied, and diagnosis remains challenging in many cases. We present a case series of four patients in whom diagnosis of Entamoeba histolytica highlight the challenges and pitfalls of diagnosing amoebic colitis in developed countries where the incidence is low.